An investigation of the skills and knowledge required by management accountants to fulfil their new job role that accompanies an ERPS implementation - Richardson, Faye (2007)
The utilization of enterprise resource planning systems (ERPS) has become widespread in recent years and research has focused on the consequences of their implementation. Such consequences that accompany the implementation of an ERP system have included a change in the role of management accountants. This research uses interviews within one international firm (Firm X) to further investigate the changes to the role of management accountants. After identifying a firm where the role of management accountants has changing appropriately, it investigates the skills and knowledge required to fulfil these new roles, whether accountants have coped with the role change and how firms have assisted with the change in role. The implementation of the ERP system within firm X has been accompanied by an appropriate change in the role of management accountants. The ERP system reduced the time spent taken on routine tasks and allowed more time to conduct deeper analyses. The management accountants have migrated to work within cross functional product teams using their specialist knowledge to assist with strategy and business support. The interviewees indicated that certain skills and knowledge became more essential to have to fulfil these roles. These included technical skills including IT and accounting skills, soft skills such as communication, persuasion and teamwork as well as a need for greater awareness of the business and the work of other departments. Being proactive and a willingness to work within that type of role were also required. The research indicated that most of the management accountants within the firm appeared to have coped with the need for these skills however they had not been provided with any specific training or assistance to help develop the new skills. They did however already have knowledge to perform the deeper analysis from the accounting qualifications and IT training and general workshops were available to help with the new system. The researcher suggests that more specific training could be offered to help the management accountants fulfil these roles more successfully, especially to develop softer skills. However this research merely represents a starting point and ends with a call for accompanying research in the same area. The researcher suggests more in depth empirical research across a larger sample size allowing the skills to be ranked in importance allowing managers to target skills training more specifically.